Believe me : a memoir of love, death, and jazz chickens - Izzard, Eddie; Zigman, Laura (Blue Rider Press, 2017)
"Critically acclaimed, award-winning British comedian and actor Eddie Izzard details his childhood, his first performances on the streets of London, his ascent to worldwide success on stage and screen, and his comedy shows which have won over audiences around the world"--